Analisis Faktor-Faktor yang Mempengaruhi Kinerja Sistem Informasi Akuntansi pada LPD di Kecamatan Petang - I Kadek Aryawan; I Ketut Sunarwijaya; Ni Putu Lisa Ernawatiningsih (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2023)
Since the evening LPD plays a role for the community, the LPD should continue to improve its performance every day in order to improve the well-being of the community. In order for LPD to best serve its customers, LPD managers must make wise use of developments in information technology. The population of this survey is all his LPD staff throughout the Petang District and units related to Accounting Information Systems. The sample for this survey was determined by a targeted sampling method with a total of 66 respondents, and the data for the survey were obtained from the questionnaire distribution results and analyzed using multiple linear regression methods. As a result, the top management's support did not affect the performance of LPD's accounting information system in Petang Province, and the formalization of system development did not affect the performance of LPD's accounting information system in Petang Province. The quality of the information system had a positive impact on the performance of his LPD's accounting information system in Petang district, and the size of the organization had a positive effect on the performance of his LPD's accounting information system in Petang district. The existence of the Steering Committee does not affect the performance of the accounting information system of the Pétain District LPD.